2007
DOI: 10.1111/j.1365-2044.2007.05055.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol infusion syndrome

Abstract: SummaryThe clinical features of propofol infusion syndrome (PRIS) are acute refractory bradycardia leading to asystole, in the presence of one or more of the following: metabolic acidosis (base deficit > 10 mmol.l−1), rhabdomyolysis, hyperlipidaemia, and enlarged or fatty liver. There is an association between PRIS and propofol infusions at doses higher than 4 mg.kg−1.h−1 for greater than 48 h duration. Sixty‐one patients with PRIS have been recorded in the literature, with deaths in 20 paediatric and 18 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
279
4
22

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(322 citation statements)
references
References 63 publications
6
279
4
22
Order By: Relevance
“…Although there are no data supporting any particular drugs or regimens, propofol should not be used for long-term sedation in children younger than 3 years because of the reported association with fatal metabolic acidosis. The use of etomidate and/or dexmedetomidine during septic shock should be discouraged, or at least considered carefully, because these drugs inhibit the adrenal axis and the sympathetic nervous system, respectively, both of which are needed for hemodynamic stability [617][618][619][620].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Although there are no data supporting any particular drugs or regimens, propofol should not be used for long-term sedation in children younger than 3 years because of the reported association with fatal metabolic acidosis. The use of etomidate and/or dexmedetomidine during septic shock should be discouraged, or at least considered carefully, because these drugs inhibit the adrenal axis and the sympathetic nervous system, respectively, both of which are needed for hemodynamic stability [617][618][619][620].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Patients should be monitored closely for the presence of elevated triglycerides and lactic acidosis [43]. PRIS leads to characteristic symptoms and clinical signs, including hepatomegaly, severe metabolic acidosis, rhabdomyolysis, hyperkalemia, acute kidney injury, dyslipidemia, and progressive myocardial failure with dysrhythmias [44]. Most patients with PRIS present with severe metabolic acidosis with elevated lactate levels and metabolic alkalosis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Despite this, the American College of Critical Care Medicine 6 recommends checking triglyceride levels after 2 days, and European regulatory authorities suggest monitoring for metabolic acidosis, rhabdomyolysis, hyperkalemia, and heart failure. 8 Case studies 2 have shown that stopping propofol administration can reverse impending PRIS at an early stage. Once in full swing, the hemodynamic instability is refractory to fluids and inotropes.…”
Section: Clinical Presentation Of Propofolrelated Infusion Syndromementioning
confidence: 99%
“…4 Various mechanisms have been proposed for the pathophysiology of PRIS. 2,5 To summarize, propofol impairs function of the mitochondrial respiratory chain. The impaired production of mitochondrial adenosine triphosphate and presence of soya bean (added to enhance solubility of propofol) increase triglyceride load.…”
Section: Introductionmentioning
confidence: 99%